2021
DOI: 10.29057/esh.v9i18.6283
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo Local en la Era Post Covid-19

Abstract: El objetivo del presente trabajo es especificar un modelo para el estudio de los efectos del cambio climático sobre la salud pública y el Desarrollo Local. Para tal propósito, se llevó a cabo un estudio documental con una muestra de fuentes indexadas con registro ISSN y DOI publicadas durante el periodo 2010 a 2021. Posteriormente, la información fue procesada en matrices de análisis de contenido a fin de poder establecer los ejes de discusión y temas de debate en la agenda investigativa. Por último, considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Framing studies warn that verifiability is generated in sources that seek to sustain a narrative in the face of an uncertain and prolonged event [34]. In the present work it is appreciated that verifiability was the first strategy of the printed media to spread the pandemic [35]. Verisimilitude studies have shown that this framework emerges once the audiences have given up seeking information from different sources because they consider that the problem or risk event has been controlled [36].…”
Section: Discussionmentioning
confidence: 83%
“…Framing studies warn that verifiability is generated in sources that seek to sustain a narrative in the face of an uncertain and prolonged event [34]. In the present work it is appreciated that verifiability was the first strategy of the printed media to spread the pandemic [35]. Verisimilitude studies have shown that this framework emerges once the audiences have given up seeking information from different sources because they consider that the problem or risk event has been controlled [36].…”
Section: Discussionmentioning
confidence: 83%
“…The Delphi technique was used to homogenize the meanings of words included in the items on the scale [23]. The surveys were applied in the social work office of the general hospital.…”
Section: Processmentioning
confidence: 99%
“…A long debate was generated for the variable to achieve this status, contrary to the establishment of its dimensions. Thus, the transition from a 40-year-old psychology of sustainability to a psychology of water services could take the same number of years [27]. From now on, it is possible to outline some axes, trajectories and relationships between the variables that are subtracted from the social, community, political, health.…”
Section: Introductionmentioning
confidence: 99%